V-FUZZY b-METRIC SPACE AND RELATED FIXED-POINT THEOREM - Happy Hooda, Manjeet Rathee, Archana Malik, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The paper concerns our sustained efforts for introduction of V-fuzzy b-metric spaces and to study their basic topological properties. As an application of this concept, we prove coupled common fixed-point theorems for mixed monotone maps in partially ordered V-fuzzyb-metric spaces.